Kepimpinan Pengetua cemerlang di sekolah menengah di daerah Muar Johor - Jasni, Ayunni (2013)
This study was conducted with the aim to study the outstanding principal leadership. This study also aimed to identify the teachers' view of the Outstanding Principal, the prerequisites necessary to become an excellent principal, balancing the extent of the humanitarian aspects and duties of the Principal Outstanding Leadership, Outstanding Principal role to bring the changes in schools, improving Outstanding Principal evaluation criteria and how Outstanding Principal help other principals to improve their school performance. A mix method study was conducted with three respondents of Outstanding Principals and 142 teachers who were selected by the school management. The study involved data collection using questionnaires and interviews. A pilot study was conducted where the total Alpha Chronbach coefficienct value was 0.955, meanwhile the Alpha Chronbach coefficienct values for the task and relationship dimensions were 0.849 and 0.962 respectively. So, the questionnaire was suitable to be used for this study. The results of the survey showed that the task dimension had a higher mean value than the relationship dimension. The qualitative findings revealed several pre-requisites which were needed prior to becoming an Outstanding Principles. Besides that, several esspential which spend be performed by Outstanding Principles were also indetified to ensure changes could be brought to school.